Continuous swaging of composite wire bundles through controlled material flow. Issue 1 (2022) - Groche, Peter; Löffler, David; Franceschi, Alessandro; Chi, Fansun
Abstract: Due to their enhanced mechanical and magnetic properties, composite wire bundles play a central role in many industrial areas. For the production of these parts, continuous metal forming processes with stationary conditions are economically advantageous and enable large-scale production. However, the different mechanical properties of the materials used in the composite rods often make a continuous process execution a technological challenge. The paper at hand investigates the process limits of swaging operations of wire bundles via analytical, numerical and experimental methods. The knowledge gained about the effect of process parameters on the material flow enables a favourable process design.